ENHANCING INDEPENDENT LEARNING STRATEGIES IN TEACHING ENGLISH THROUGH CASE STUDIES - Aripova Saodat Tohirovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article discuss about enhancing independent learning strategies in teaching English through case studies.